Antibacterial Efficacy of Aloe vera Sap Against Staphylococcus aureus and Escherichia coli - Safira Azahra; Nita Parisa; Fatmawati Fatmawati; Ella Amalia; Venny Larasati (HM Publisher, 2019)
Abstract Background Aloe vera is a plant that has been used as an alternative drug. This plant contains various compounds, like anthraquinone, saponin, flavonoid, alkaloid, and tannin that has an antibacterial effect against Staphylococcus aureus and Escherichia coli. Both of it were responsible for the infection incident. This study aims to determine the efficacy of Aloe vera sap as an antibacterial against Staphylococcus aureus and Escherichia coli. Methods An experimental study, in vitro using post-test only control group design, has been done at laboratory of Medical Faculty of Sriwijaya University, by examining the antibacterial activity of Aloe vera sap in five different concentration (5%, 10%, 20%, 40%, dan 80%) using well diffusion and solid dillusion method to determine the minimum bactericidal concentration (MBC). And then continued with the phytocemical screening to determine the compound inside the Aloe vera sap. Results Aloe vera sap were able to kill Staphylococcus aureus at 5% and Eshcerichia coli at 80%. Compatibility test showed that Aloe vera sap with concentration of 10%, 20%, 40%, and 80% are compatible with amoxicillin, therefore 80% is compatible with cefotaxime. This ability due to the compound that it contains, which is alkaloid, flavonoid, tannin, quinone, and saponin. Conclusion Aloe vera sap is effective as an antibacterial against Staphylococcus aureus and Escherichia coli. Keyword: Aloe vera sap, antibacterial, efficacy, Staphylococcus aureus, Escherichia coli.